PENINGKATAN HASIL BELAJAR MATEMATIKA BERBASIS KECERDASAN LOGIS-MATEMATIS MELALUI MODEL QUANTUM TEACHING PADA SISWA MTs SWASTA AL-HUDA PANGKALAN SUSU - Humairoh; R, I, Iden; A, Rizki (Jurnal Dimensi Matematika, 2023)
This study aims to determine the improvement of mathematics learning outcomes based on logical-mathematical intelligence through the quantum teaching model in MTs Swasta Al-Huda Pangkalan Susu students. The type of research used in this study is One Group Pretest-Posttest Design. The population in this study were all VII grade students of MTs Swasta Al-Huda Pangkalan Susu consisting of three classes, namely VII-1 to VII-3, totaling 95 students. The sample used was all students of class VII-2 as many as 32 students. The instruments used were written tests and observation sheets. Based on the results of student research data using the wilcoxon test because the data is not normally distributed. Statistical results that have been carried out obtain an asymp.Sig.(2-tailed) value of 0,000. Therefore, 0,000 < 0,05 H0 is rejected and H1 is accepted. So it is concluded that there is an increase in mathematics learning outcomes based on logical-mathematical intelligence after experiencing learning by using the quantum teaching model at MTs Swasta Al-Huda Pangkalan Susu on set operation material.